2020
DOI: 10.1098/rspb.2019.2969
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile rank acquisition is associated with fitness independent of adult rank

Abstract: Social rank is a significant determinant of fitness in a variety of species. The importance of social rank suggests that the process by which juveniles come to establish their position in the social hierarchy is a critical component of development. Here, we use the highly predictable process of rank acquisition in spotted hyenas to study the consequences of variation in rank acquisition in early life. In spotted hyenas, rank is ‘inherited’ through a learning process called ‘maternal rank inheritance.’ This pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 54 publications
(74 reference statements)
0
37
2
Order By: Relevance
“…consistently predict either its ARS or its longevity. Although it has been well-documented that maternal rank affects juvenile survivorship in this species (Strauss, Shizuka, & Holekamp, 2020;Watts et al, 2009), of those hyenas who survived past 3 years of age in our study, their ranks early in life did not always predict their fitness in adulthood. However, regardless of the rank an individual held early in life, its early social position within its network strongly influenced its ARS and longevity.…”
Section: Social Position During Ontogeny Predicts Fitnesscontrasting
confidence: 78%
“…consistently predict either its ARS or its longevity. Although it has been well-documented that maternal rank affects juvenile survivorship in this species (Strauss, Shizuka, & Holekamp, 2020;Watts et al, 2009), of those hyenas who survived past 3 years of age in our study, their ranks early in life did not always predict their fitness in adulthood. However, regardless of the rank an individual held early in life, its early social position within its network strongly influenced its ARS and longevity.…”
Section: Social Position During Ontogeny Predicts Fitnesscontrasting
confidence: 78%
“…In these species, one of the major mechanisms posited to link maternal loss with increased mortality is through the social adversity caused by mother absence. Specifically, mother absence is found to reduce social integration 5,21 , competitivity 16,22 , dominance rank 6,1820 and opportunities for social learning 8,23,24,26 . But the lack of increased mortality in gorillas and certain human populations suggests that mother absence does not always lead to social adversity in mammals with extended maternal care.…”
Section: Discussionmentioning
confidence: 97%
“…In social mammals the removal of maternal care due to maternal loss can reduce survival in the youngest offspring 3 by affecting for example nutrition, thermoregulation and protection 4 . But maternal loss can also reduce the fitness of offspring in a far broader age range through long-term effects on their social environment, negatively influencing their social integration and social status throughout their lives 1,5,6 . Multiple studies have now confirmed effects on survivorship for individuals orphaned well past the period of nutritional dependency, with these negative changes to their social environment, often termed social adversity, posited to be the key mechanism by which this occurs 5,710 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, mothers are essential for the early development of their infants since they provide post-natal care (Maestripieri & Mateo 2009). Maternal loss in mammals reduces growth (Samuni et al 2020), survival (Watts et al 2009;Andres et al 2013;Tung et al 2016;Stanton et al 2020), and long-term reproductive success (Andres et al 2013;Strauss et al 2020;Crockford et al 2020, reviewed in Clutton-Brock 2016. The biological embedding model (Power & Hertzman 1997;Miller et al 2011;Berens et al 2017) posits that adversity experienced early in life, including exposure to severe stressors, can have deleterious consequences on an individual's physiology and health across their lifespan.…”
Section: Introductionmentioning
confidence: 99%